Hardness Recognition of Robotic Forearm Based on Semi-supervised Generative Adversarial Networks - Qian, Xiaoliang; Li, Erkai; Zhang, Jianwei; Zhao, Su-Na; Wu, Qing-E; Zhang, Huanlong; Wang, Wei; Wu, Yuanyuan (Frontiers in Neurorobotics, 2019)
The hardness recognition is of great significance to tactile sensing and robotic control. The hardness recognition methods based on deep learning have demonstrated its good performance, however, a huge amount of manually labeled samples which require lots of time and labor costs are necessary for the training of deep neural networks. In order to alleviate this problem, a semi-supervised generative adversarial networks (GAN) which requires less manually labeled samples is proposed in this paper. First of all, a large number of unlabeled samples are made use of through the unsupervised training of GAN which is used to provide a good initial state to the following model. Afterwards, the manually labeled samples corresponding to each hardness level are individually used to train the GAN of which the architecture and initial parameter values are inherited from the unsupervised GAN, and augmented by the generator of trained GAN. Finally, the hardness recognition network (HRN) of which the main architecture and initial parameter values are inherited from the discriminator of unsupervised GAN is pretrained by a large number of augmented labeled samples, and fine tuned by manually labeled samples. The hardness recognition result can be online obtained by importing the tactile data captured by the robotic forearm into the trained HRN. The experimental results demonstrate that the proposed method can significantly save the manual labeling work while providing an excellent recognition precision for hardness recognition.